Robust Lateral and Longitudinal Control for Vehicle Platoons With Unknown Interaction Topology Subject to Multiple Communication Delays - Zhang, Nianhua; Li, Xiang; Chen, Jicheng; Li, Hongbiao; Nie, Yiming; Zhang, Hui (IEEE transactions on intelligent vehicles, 2024)
This article addresses the lateral and longitudinal control problem for vehicle platoons subject to multiple communication delays. The essential lateral control problem and different delays in search-based routes of the vehicular ad-hoc networks (VANET) are introduced to vehicle platoon control. We first design an objective-based decoupled lateral and longitudinal control framework for vehicle platoons. With the Frenet coordinate system, a robust controller for lateral control is established to ensure each follower vehicle tracks the desired path and remain within the platoon. For the longitudinal control, the longitudinal error dynamic of vehicle- i with a specific interacted vehicle- j is modeled. Furthermore, with an unknown interaction topology, the error dynamic is augmented as multiple low-dimensional subsystems instead of an high-dimensional platoon system. To accommodate the communication delays, we design a distributed robust controller based on the Lyapunov-Krasovskii function. In addition, a delay-tolerant controller design theorem is obtained with linear matrix inequalities (LMIs). Simulations are conducted to demonstrate the effectiveness and improvement of the proposed controllers.